Towards the Discourse of Islamic Philanthropy for Social Justice in Indonesia Ariza Fuadi - Ariza Fuadi (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2012)
The rapid development of Islamic philanthropic activism in Indonesia has drawn much attention among scholars, practitioners, and policy makers. It appears that efforts to promote Islamic philanthropic activism as a means of fostering social justice have been done by civil society organizations and the state’s agencies. It can be seen partly in the motives and objectives of Islamic philanthropic associations, as well as regulations enacted by the state regarding the practice of Islamic philanthropy since independent era until nowadays. It suggests that the philanthropic culture in Muslim societies is no longer governed in a traditional way, or simply to relieve the poor. Instead, it is expected that through the culture of giving, poverty can be alleviated, and Islamic associations can provide long-term development projects. However, in reality, these efforts to promote social justice have been constrained by several factors, including social, economic and political factors, and therefore enduring and systematic efforts from the state’s actors and civil society, to promote social justice are, still needed. Keywords: philanthropy, Islam, social justice.